Studi Feminis dalam Agama : Melintas Batas dan Mendobrak Tradisi Agama Patriarki - Paskalis Yuven Atabau (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This article examines the study of feminism and Christianity. Feminist studies in religion try to reveal the reality of oppression and discrimination and fight for the liberation of women. This research aims to analyze feminist studies in religion. This research method uses a library research approach to explore the study of feminism and religion. The results of this study, namely; first, doctrines and traditions in Christianity have interventions in the practice of injustice against women. Second, feminist studies in religion try to fight for a liberation agenda for women by offering a feminist approach in interpreting Scripture. Third, the struggle of feminism in religion is still trapped in the categories of race and class. This paper proposes an idea of women's solidarity and cross-border struggle. All women unite and are open to accepting differences in order to realize the liberation agenda. The struggle must cross the boundaries of group, community, class and race.